For the sake of the argument Ramsey test conditionals, inductive inference, and nonmonotonic reasoning - Levi, Isaac 1930-2018 (Cambridge Univ. Press, 1996)
In arguing that the distinction between belief contravening and inductive nonmonotonicity plays a far greater role in deliberation and decision than it is given credit for, this major study will be required reading for all philosophers and logicians concerned with conditionals, decision theory, and inductive inference. It will also interest those in artificial intelligence who work on expert systems, default reasoning, and nonmonotonic reasoning